Seacoast Marshelder, Iva imbricata - Debbie Miller; Mack Thetford; Chris Verlinde; Gabriel Campbell; Ashlynn Smith (EDIS, 2018)
Seacoast marshelder is an important plant for dune restoration, stabilization, and formation because of its ability to trap sand. It grows on foredunes and forms low, rounded dunes as sand accumulates (Craig 1991). As the aboveground portions of the plant become buried by sand, rooting is stimulated in stem tissue (Craig 1975). This gives the appearance that the plant is rhizomatous when in fact it is the sand burial resulting in the presence of below-ground stems. This plant occurs throughout coastal Florida (except for the Big Bend coast) and in coastal southeastern states west to Texas and northeast to Virginia. https://edis.ifas.ufl.edu/sg174